2017
DOI: 10.3329/jbcps.v35i2.33368
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sodium Bicarbonate to Treat Neonatal Metabolic Acidosis: Beneficial or Not

Abstract: Despite the lack of evidence for effectiveness of sodium bicarbonate in treatment of metabolic acidosis in critically ill patients who are admitted in neonatal and pediatric intensive care unit, bicarbonate administration is a common practice and has a long history of widespread use. The justification for persistent use of this controversial therapy comes from a variety of sources, many of them based in philosophy than in science. Clinicians must consider the intervention which will meet the therapeutic object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…[21] Whereas the data of our study showed that even though ISB worsens intracellular acidosis, increases myocardial injury, contributes to intracranial hemorrhage, and decreases oxygen transport to tissues, it is nevertheless often administered as a treatment for MA in new-born intensive care. [10] Our results showed that most participants (80.6%) use normal saline fluid boluses to manage MA rather than the routine administration of ISB. However, according to the Cochrane Database of Systematic Reviews, there is currently insufficient evidence to support the routine intravenous bolus administration of albumin or normal saline to normovolumic neonates suffering MA.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…[21] Whereas the data of our study showed that even though ISB worsens intracellular acidosis, increases myocardial injury, contributes to intracranial hemorrhage, and decreases oxygen transport to tissues, it is nevertheless often administered as a treatment for MA in new-born intensive care. [10] Our results showed that most participants (80.6%) use normal saline fluid boluses to manage MA rather than the routine administration of ISB. However, according to the Cochrane Database of Systematic Reviews, there is currently insufficient evidence to support the routine intravenous bolus administration of albumin or normal saline to normovolumic neonates suffering MA.…”
Section: Discussionmentioning
confidence: 67%
“…[5,9] In order to reduce morbidity and mortality and correct MA, SB has been utilized for many years as a treatment for critically ill neonates with metabolic acidemia to reverse MA during newborn resuscitation. [10]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations